EFEKTIVITAS STRATEGI INVESTASI PASIF DAN AKTIF DI PASAR MODAL INDONESIA: DAMPAKNYA TERHADAP KINERJA PORTOFOLIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Asri, Sukma; Missel, Rheinata Audreyna; Pandin, Maria Yovita R. (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
This study analyzes the effect of passive and active investment strategies on the portfolio performance of manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2022. Secondary data were obtained from the annual reports of 10 companies, with regression analysis using SPSS. The results show that there is no significant difference between the two strategies in affecting portfolio performance, although companies with active strategies have a higher average share value. The high volatility of the Indonesian market and higher transaction costs of the active strategy explain this result. Thus, the passive strategy is more recommended for investors who seek portfolio management with lower risk and cost in the long run.